Optimization of Cryosoaking Period and Microstructural Transformation on Wear Mechanism of SAE 8620 Gear Steel. Issue 6 (2nd November 2017) - Ghosh, P.; Dhokey, N. B.
ABSTRACT: Rotating parts such as gears and shafts are invariably subjected to wear. The observed frequent failure of these transmission elements led to this experimental study on the wear resistancel. In the current research study, specimens of gear steel (SAE 8620) were austenized at 1193 K followed by oil quenching and subsequent tempering at 473 K. These steels were soaked at 88 K for different lengths starting from 4 to 20 h of cryosoaking followed by soft tempering at 373 K. Specimens were characterized for microstructural analysis using optical microscopy, scanning electron microscopy (SEM), and retained austenite content by X-ray diffraction (XRD). Optimized cryotreated specimens were then compared with conventionally treated specimens for wear behavior and worn surface analysis. Worn surfaces of wear specimens at varying loads (4 and 10 kg) and sliding speeds (2 and 3.5 ms −1 ) were examined to identify the mechanism involved during wear. The 2D contour map was interpreted for hardened tempered (HT) and hardened tempered cryotreated HTC (16 h) specimens and the prevailing wear mechanism was explored followed by establishing a correlation with microstructural transformation.